2014
DOI: 10.1088/2041-8205/792/1/l22
|View full text |Cite
|
Sign up to set email alerts
|

An Enigmatic Point-Like Feature Within the Hd 169142 Transitional Disk,

Abstract: We report the detection of a faint pointlike feature possibly related to ongoing planetformation in the disk of the transition disk star HD 169142. The pointlike feature has a ∆mag(L)∼6.4, at a separation of ∼0.11 ′′ and PA∼0 • . Given its lack of an H or K S counterpart despite its relative brightness, this candidate cannot be explained by purely photospheric emission and must be a disk feature heated by an as yet unknown source. Its extremely red colors make it highly unlikely to be a background object, but … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
143
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 139 publications
(152 citation statements)
references
References 45 publications
6
143
3
Order By: Relevance
“…Recently, several discoveries of (candidate) low-mass companions (low-mass stars and protoplanets) embedded in the circumstellar disk of young stars were announced: around LkCa 15 (Kraus & Ireland 2012), HD 142527 (Biller et al 2012), HD 100546 (Quanz et al 2013), and HD 169142 (Reggiani et al 2014;Biller et al 2014). While the exact nature of some of these sources needs to be further investigated, some of these objects are probably indeed observed in the act of formation as indicated by the Hα emission of LkCa 15 b Sallum et al (2015) (see also HD 142527B, Close et al 2014).…”
Section: The Planetary Mass -Luminosity Relationmentioning
confidence: 99%
“…Recently, several discoveries of (candidate) low-mass companions (low-mass stars and protoplanets) embedded in the circumstellar disk of young stars were announced: around LkCa 15 (Kraus & Ireland 2012), HD 142527 (Biller et al 2012), HD 100546 (Quanz et al 2013), and HD 169142 (Reggiani et al 2014;Biller et al 2014). While the exact nature of some of these sources needs to be further investigated, some of these objects are probably indeed observed in the act of formation as indicated by the Hα emission of LkCa 15 b Sallum et al (2015) (see also HD 142527B, Close et al 2014).…”
Section: The Planetary Mass -Luminosity Relationmentioning
confidence: 99%
“…It also seems likely that the formation of planetary embryos (if they form at all) precedes the transition disk phase, since it makes more sense for these objects to form in the long period when sufficient mass was available, rather than during the short transition phase during which that mass was depleted. Moreover there is some observational evidence for planets or companions in transition disks (Huélamo et al 2011;Kraus and Ireland 2012;Quanz et al 2013;Biller et al 2014;Reggiani et al 2014), and the gas giant planets seen around many main sequence stars must have formed in the presence of significant quantities of gas.…”
Section: Physical Distinctionmentioning
confidence: 99%
“…These discoveries show HD 169142 to be among the first objects in which multiple gaps have been found. A point-like IR source, possibly a brown dwarf or a forming planet, was found at ∼23 au from the central star, that is, just at the inner rim of the outer disk (Biller et al 2014;Reggiani et al 2014). With radio observations at 7 mm, Osorio et al (2014) confirmed that the second gap is likely to be caused by a dip in surface density profile, and found a possible point source in this gap region.…”
Section: Introductionmentioning
confidence: 99%